Antiurolithiatic Activity of Extract and Oleanolic Acid Isolated from the Roots of Lantana camara on Zinc Disc Implantation Induced Urolithiasis. (15th May 2013) - Vyas, Narendra; Argal, Ameeta
Abstract : The present study was done to evaluate the antiurolithiatic activity of ethanolic extract of roots (ELC 200 mg/kg) and oleanolic acid (OA 60 mg/kg, O.A. 80 mg/kg, O.A. 100 mg/kg) isolated from roots of Lantana camara in albino wistar male rats using zinc disc implantation induced urolithiatic model. The group in which only zinc disc was implanted without any treatment showed increase in calcium output (23    ±   2.7  mg/dL). Cystone receiving animals showed significant protection from such change (P < 0.01 ). Treatment with OA and ELC significantly reduced the calcium output at a dose of OA 60 mg/kg (P < 0.01 ), OA 80 mg/kg (P < 0.01 ), ELC 200 mg/kg (P < 0.01 ), and OA 100 mg/kg (P < 0.001 ), as compared with zinc disc implanted group. The average weight of zinc discs along with the deposited crystals in the only disc implanted group was found to be111 ± 8.6  mg. Group that received Cystone 500 mg/kg showed significant reduction in the depositions (P < 0.001 ). Similarly, the rats which received OA and ELC showed reduced formation of depositions around the zinc disc (P < 0.001 ). The X-ray images of rats also showed significant effect of OA and ELC on urolitiasis. Thus, OA and ELC showed promising antiurolithiatic activity in dose dependant manner.